A history of Japanese astronomy : - Nakayama, Shigeru (Harvard University Press, 1969)
This first comprehensive history in a Western language of the development of Japanese astronomy has interest beyond its immediate subject area, for astronomy has often been the focus of the transmission of a wide range of scientific ideas from one culture to another, and, concomitantly, the focus of conflict between opposing modes of thought.